5-PUB: Retrospective Study of Patients with Dyslipidemia With and Without Type 2 Diabetes Mellitus Treated with a Fixed-Dose Combination of Rosuvastatin/Ezetimibe - RODRIGUEZ VAZQUEZ, ILEANA C.; RIOS-BRITO, KEVIN F.; SANDER-PADILLA, JOSE G.; RODRIGUEZ-ROCANDIO, KARLA E.; LUGO-SÁNCHEZ, LAURA A.; ARGUEDAS, MARÍA M.; FLORES-HUANOSTA, DIANA; GONZALEZ-CANUDAS, JORGE; ROMERO, YULIA (Diabetes (New York, N.Y.), 2024)
Introduction and Objective: Currently, dyslipidemia is one of the most common comorbidities in patients with Type 2 Diabetes Mellitus (T2DM), for which cardiovascular risk (CVR) is usually underestimated, being this the case where the use of combined therapy of statins and ezetimibe is considered one of the best options. The aim of the study was to evaluate a cohort of patients with dyslipidemia with and without T2DM treated with a fixed-dose combination (FDC) of rosuvastatin/ezetimibe. Methods: Retrospective study, in patients with dyslipidemia with and without T2DM treated with FDC rosuvastatin/ezetimibe (10/10 or 20/10 mg once daily). Information was collected retrospectively, from patients' clinical records, including complete biochemical results and lipid profile from three visits (baseline, 2 and 4 months). Mann Whitney U and chi-square tests were performed for comparisons between groups, with SPSS 29v. statistical program. Results: Data from 103 patients was collected (55.4% men), mean age of 56 years and body mass index (BMI) of 28.4 Kg/m2. Patients' median baseline glucose was 145mg/dL (IQR: 118; 228), and 138 mg/dL (IQR: 112.6; 191.5) for final follow-up visit for the group with T2DM (n=33), 90mg/dL (IQR: 86.2; 97.6) and 93mg/dL (IQR: 89.0; 97.0) for the no T2DM group (n=57), respectively. For the observed target values, by the end of follow-up 29% of patients without T2DM and 20% with T2DM had achieve triglyceride levels <150mg/dL (p= 0.001), while 36.8% vs 50.5%, respectively had achivied LDL-C levels <100mg/dL (p= 0.056) at the final visit. FDC treatment exhibited an appropriate safety profile. Conclusion: FDC rosuvastatin/ezetimibe has shown a significant clinical impact on lipid profile biomarkers in patients with dyslipidemia with and without T2DM, mainly in the achievment of LDL-C reduction of <100mg/dL.